2017
DOI: 10.1007/s00126-016-0706-4
|View full text |Cite
|
Sign up to set email alerts
|

Weathering of PGE sulfides and Pt–Fe alloys in the Freetown Layered Complex, Sierra Leone

Abstract: Fresh and weathered rocks and saprolite from Horizon B of the Freetown Layered Complex contain platinum-group minerals (PGM). The PGM in the fresh rocks are 1-7 μm across, including cooperite (PtS), isoferroplatinum (Pt 3 Fe), minor tetraferroplatinum (PtFe), tulameenite (Pt 2 FeCu), Os-bearing laurite (RuS 2 ), and other base metalsulfide (BMS)-bearing PGM. The weathered rocks contain fewer of those PGM but a high proportion of disordered Cu-(±Pd)-bearing Pt-Fe alloys. The saprolite hosts scarce, smaller (1-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…The rocks beneath the sample site consist of a layered gabbroic sequence within which there is a PGE-enriched horizon containing small, weathered PGM [1, 2,26]. The PGM are disseminated with rare minute Cu-sulfides.…”
Section: The Sample Sitementioning
confidence: 99%
See 2 more Smart Citations
“…The rocks beneath the sample site consist of a layered gabbroic sequence within which there is a PGE-enriched horizon containing small, weathered PGM [1, 2,26]. The PGM are disseminated with rare minute Cu-sulfides.…”
Section: The Sample Sitementioning
confidence: 99%
“…The humic and fulvic acid contents of a sample from that soil have been examined previously [12,13]. A comparison of the geochemistry of the rocks, saprolite, and soil has indicated that Pt, Pd and Au are mobile within the saprolite and soils [2]. The saprolite that covers the PGE-enriched horizon contains Pt, Pd, and Au.…”
Section: The Sample Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Weathering of these rocks does not produce a gossan. Comparison of the geochemistry of the rocks, saprolite and soil has indicated that Pt, Pd and Au are mobile within the saprolite and soils [2].There is a shallow soil, normally about 10 cm in thickness and a sample from that soil has been examined previously [12,13]. The thin soil overlies saprolite derived from weathering of the layered rocks.…”
Section: The Sample Sitementioning
confidence: 99%
“…Platinum-group minerals (PGM) have been located in these rocks and shown to have been altered by superficial weathering [1,2]. Alluvial PGM have been recovered from the streams draining the intrusion and they are notably different in mineral assemblage, composition, and size from the PGM in the unaltered host rocks [3,4].…”
Section: Introductionmentioning
confidence: 99%